Associação entre comportamentos de risco à saúde de pais e irmãos e de adolescentes escolares de zona rural - Raphaelli, Chirle de Oliveira (2011)
Among the risk factors associated with noncommunicable diseases and injuries (DANTS), include those related to lifestyle, especially smoking, physical inactivity, poor diet and alcohol abuse. Adolescence is a particularly relevant in determining dants, whereas behaviors and habits acquired at this stage tend to persist into adulthood. Moreover, the behavior of risk the health of parents and siblings can influence health risk behavior of adolescents. Objectives: To evaluate the association between health risk behaviors among adolescent schoolchildren and their parents and siblings living in a rural area of the municipality of Rio Grande do Sul. Methodology: Cross-sectional study in a rural area in the town of Barão do Triunfo / RS . The sample will include young students from 5th to 8th grades in the municipal education, their parents and siblings at the age of adolescence (10-19 years). Will be collected on the adolescents, their parents and siblings, health risk behaviors (physical inactivity, cigarette smoking, alcohol consumption, poor eating habits and excess weight) in addition to socioeconomic, demographic and health of the population studied . For data collection the students were included questions about the work situation, and to measure the body fat percentage. Analysis Statistics: A description of the studied population, including the pertaining to school, parents and brothers, will be lead according to demographic, socioeconomics characteristics, mannering nutricionais and of health. The association between the studied outcomes and the independent variable will be evaluated with the test of Qui-square for heterogeneidade or linear trend. Relevance: With the data from this study, we have scientific grounds to carry out interventions and plan prevention strategies in the medium and long term in order to promote changes in habits and behaviors related to lifestyle for the whole family.